An Open‐Label Phase 2a Study to Evaluate the Safety and Tolerability of Perampanel in Cervical Dystonia. Issue 5 (13th May 2021) - Fox, Susan H.; Swan, Matthew; Jinnah, Hyder A.; de Freitas, Maria E.T.; de Oliveira, Lais M.; Al‐Shorafat, Duha; Fernandez, Hubert H.; Kompoliti, Katie; Comella, Cynthia
ABSTRACT: Background: Cervical dystonia (CD) is the most common focal isolated dystonia. Preclinical studies report that AMPA‐selective glutamate receptor antagonists improve dystonia. Perampanel is a clinically available, AMPA receptor antagonist that has shown efficacy and safety in epilepsy. Objectives: To determine safety and tolerability of perampanel in CD. Methods: We performed a phase 2a, open‐label, multicenter study to evaluate tolerability and safety of perampanel in CD. Included subjects had primary CD; those on botulinum toxin were 8 weeks post last injection. All subjects received perampanel 2 mg/day, titrated 2 mg weekly over 6 weeks, to maximum 12 mg/day; maintenance phase was 4 weeks, ending at week 10. Primary endpoints included tolerability, defined as ability to remain on perampanel for the maintenance period, at any dose level and safety, determined from adverse events (AEs) collected at each visit. Secondary exploratory endpoints included Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS), quality of life (cervical dystonia impact profile [CIDP]‐58) and Clinical Global Impression of change (CGI). Results: CD participants (n = 25) were recruited. Eight subjects withdrew; 4 because of AEs, 3 for other reasons and 1 lost to follow up. One subject tolerated 12 mg/day. Eight subjects (30.8%) tolerated 2 mg, whereas 19.2% tolerated 4 mg/day, and 15.4% tolerated 6 mg or 8 mg/day. All subjects experienced AEs. The most common AEs were dizziness, imbalance, and irritability. Exploratory endpoints of TWSTRS showed some improved pain scores and CIDP‐58 improved sleep. Conclusions: Tolerability to perampanel was variable in CD subjects. Lower doses would be considered for future studies in this population.